Student independence crisis in distance learning during the Covid-19 pandemic - Umi Muzayanah; Zakiyah; Agus Iswanto; Wahab; Umi Masfiah (Knowledge Management & E-Learning: An International Journal)
This research aims to measure students’ learning independence levels in distance learning during the COVID-19 pandemic and identify factors that influence students’ learning independence. The quantitative method was used to obtain data from 179 high school students in Indonesia to assess students’ learning independence. In addition, this study used multiple linear regression analysis to examine the factors that influence learning independence. The result showed that student independence is at the “medium” level and strongly influenced by academic achievement, learning motivation, and time management. Furthermore, only 26.82% carried out their assignments independently, while the rest sought help from their families and copied the work of their friends. In this sense, the learning process becomes a family matter that will face challenges for the low-level income families, as most of their time is spent working to fulfill their family’s needs. Therefore, distance learning innovation is needed through diversifying learning methods and applying blended learning. The research results are useful in providing information about the impact of distance learning on students’ learning independence. Policymakers need to devise more creative and interesting learning policies to motivate students if distance learning becomes an option in the future.